Repeatedly Flashed Luminance Noise Can Make Objects Look Further Apart. (June 2019) - Born, Sabine
Luminance noise is widely used as mask in Experimental Psychology. But can luminance noise also affect where we perceive an object or change the perceived distance between objects? In this study, I investigated the effect of a repeatedly flashed luminance noise pattern on the perceived separation between two bars. Indeed, compared to conditions without dynamic luminance noise, the spacing between the bars was overestimated when the pattern flashed on-and-off in the background. The cause for this remarkably stable effect remains unknown. Potential relations to apparent motion, masking, attentional biases, and other visual illusions are discussed.